Mechanisms of Lexical Cohesion in Arabic Political Discourse: Inaugural Speeches of the Egyptian Presidents Morsi and al-Sisi - Mulović, Amra (Context: Journal of Interdisciplinary Studies, 2023)
This paper deals with the analysis of the main devices of lexical cohesion used in Arabic political discourse. We carry out the analysis applying Halliday and Hasan’s theoretical framework of cohesion. The data of the analysis consists of the inaugural speeches of two presidents of Egypt, Morsi and el-Sisi. The main goal of the research is to determine the types and function of lexical cohesion, to mark cohesive mechanisms in political speeches, and to confirm the hypothesis that the type of text and its function can indicate the extent to which certain types of cohesive ties will be used. The results of the study reveal that inaugural speech appears as a persuasive discourse and an argumentative space of dominant use of repetition, to a lesser extent synonymy, hyponymy, meronymy, antonymy and collocation, with the goals of highlighting topical issues of national relevance and promoting a certain ideology.